Towards optimised climate-smart agriculture resource investment decisions: Mapping program impact areas, policy support and mitigation feasibility - Mponela, Powell; Dzirwonu, Michael Gameli; Inusah, Sandra; Agyarko-Fosu, Fred; Odonkor, Ezekiel Narh; Sackey, Tracy Adjeley; Mamah, Samiratu Abdulai; Akpatsu, Isaac Boatey (2023)
This scoping study documents climate-smart agriculture efforts in Ghana, their scalability, and potential resilience impacts. The work fills the gap in CSA use evidence and provides a methodological approach for mapping and evaluating its feasibility. The results provide insights and evidence to support policy formulation, agenda setting and strategy development. As the saying goes, "You can't manage what you can't measure" the paucity of data and evidence on the key aspects of where, when, what, by who on CSA usage hampers implementation. The tendency has been a skewed distribution with some areas receiving more attention while other regions/districts might be sidelined. With the CGIARs Accelerating Impact of Climate Research in Africa (AICCRA) additional financing from the World Bank reported during COP28 focusing more on usage, the Alliance of Bioversity and CIAT in Ghana partnered with the Council for Scientific and Industrial Research - Institute for Scientific and Technological Information (CSIR-INSTI) develop mapping approach, database and compendium of CSAs in Ghana. The scoping study assemble evidence of past investments from government’s budgetary allocations, policies, interventions as well as the contributions of non-governmental organisations. The first section provides an overview of CSA concepts, principles and sets mapping objective. It posits that CSA requires multidisciplinary approach and aggregation of effors by multiple actors. Drawing lessons from other developing and middle income countries that have ramped up efforts to cope, mitigate and adapt to the changing climate. The second section reviews the existing policy framework including the initiatives, strategies and budgetary support. the widescale government’s CSA support has been to fertilizer and seed input supply, irrigation, legume cropping, afforestation, tree crops, cocoa and fisheries. Based on the investments, Ghana the governments capacity building and evidence of nationally determined contributions is indicative of enabling environment which attract external investments and funding. The CSA principles and assessment criteria set by FAO CSA source book and the IPCC Working Group II CSA assessment guided the study design, criteria and reporting framework. The fourth section, the CSAs are mapped for the regions indicating spatial distributions of efforts by government and non-governmental organisations. The distribution of government and NGO projects shows impact and focus areas. The predominance of projects in some regions is indicate of the adaptation need but also due to enabling conditions. The distribution of CSA systems shows the risks that CSA address which is supported by distribution of themes and CSAs. The fifth section presents the porntial and reported impacts of CSAs. The social contributions considered include use and adoption while ecological impacts include nutrient, soil and water conservation.